Smoking and Increased Symptoms of Pulmonary TB: A Retrospective Analysis at Cibinong Hospital - Fitriani, Lina; Nadirahilah; Harwati, Andriati Reny (Syntax Corporation Indonesia, 2024)
Pulmonary Tuberculosis (TB) is a contagious infectious disease that remains a global health problem. Smoking, both active and passive, is a risk factor that can worsen TB symptoms. At Seruni Ward of Cibinong Regional Hospital, many TB patients were found to be readmitted with worsening symptoms, suspected to be related to smoking history. This study aims to determine the relationship between active and passive smoking history and the worsening of pulmonary TB symptoms. The study used a quantitative correlational design with a retrospective longitudinal approach. The sample consisted of 82 pulmonary TB patients who were readmitted at least twice during 2024. Data were obtained from medical records and analyzed using the chi-square test. Results showed a significant relationship between smoking history and worsening TB symptoms (p < 0.05). Patients with an active smoking history experienced more severe symptoms. Educational and preventive interventions are needed to reduce symptom aggravation in TB patients with a smoking history.